Update in the human papillomavirus infection prevalence rates and risk factors associated with penile cancer cases - Afonso, Larissa A.; Oliveira, Ledy H.S.; Cavalcanti, Silvia Maria Baeta; Dobao, Elisabeth; Alves, Gilda (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Penile carcinoma is an uncommon and potentially mutilating disease with a still unknown etiology. Human papillomavirus (HPV) infection seems to play an important role in the development of a subset of these carcinomas and its presence is thought to be related to the histological type of the lesion. HPV prevalence in penile tumors is reported to be associated to a variety of morphological changes. In recent years, increased insight has been gained into the pathogenesis of penile cancer, the risk factors associated with penile cancer development and the clinical and histological precursor lesions related to this disease. Although penile carcinoma is recognized to be a multi-step process showing a polyclonal profile, a proportion of penile carcinoma is attributable to high risk HPV infection, while in the remaining penile cancers molecular mechanisms independent of HPV are likely to represent the more common underlying events. However, research on the mechanisms behind penile carcinogenesis is warranted.